Al-Qur’an dan Dinamika Pemikiran Islam: Tafsir Teologi Kontemporer - Amdahurifky.B (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2023)
This scientific study is about the interpretation of contemporary theology. Theology is a study that explains the divine paradigm. It is undeniable that the study of divinity cannot be separated from religious aspects. This paper tries to be more specific in examining this theological issue from the perspective of the Qur’an in this contemporary era. The method used is the interpretation of al-maudhu'i by not abandoning all aspects that can be achieved. The results achieved can provide a comprehensive explanation, especially about theology based on the interpretation of verses of the Koran. More specifically, this study describes the meanings of the Koran which speak of moderation in Islamic beliefs. This can be seen from several of its characteristics, namely in accordance with nature and reason, clear and easy, free from confusion and paradox, sturdy and timeless and not contrary to science, while the moderation of the primacy of Islamic belief in Jewish and Christian theology can be seen from several aspects, namely aspects of divinity, prophecy, Angels, Scriptures. To see in simple terms the development of Islamic thought related to contemporary theological interpretations, it can be seen from Asghar Ali Engineer's view of his theology of liberation (liberation theology).